2021
DOI: 10.3389/fonc.2021.630837
|View full text |Cite
|
Sign up to set email alerts
|

Barrett’s Esophagus and Intestinal Metaplasia

Abstract: Intestinal metaplasia refers to the replacement of the differentiated and mature normal mucosal epithelium outside the intestinal tract by the intestinal epithelium. This paper briefly describes the etiology and clinical significance of intestinal metaplasia in Barrett’s esophagus. This article summarizes the impact of intestinal metaplasia on the diagnosis, monitoring, and treatment of Barrett’s esophagus according to different guidelines. We also briefly explore the basis for the endoscopic diagnosis of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 118 publications
0
3
0
Order By: Relevance
“…Taking into account the role of acid secretion in esophageal epithelial damage, proton pump inhibitors appear to be actually the only treatment that can interfere with the worsening of histological damage. Indeed, numerous studies have shown that acid-suppressing proton pump inhibitor therapy stabilizes the activity of cellular proliferative cells in the BE and consequently can prevent dysplasia and have a positive impact on reducing the risk of cancer in the esophagus [ 61 , 62 , 63 , 64 , 65 , 66 ] especially if the therapy is continuous and long-term [ 67 ]. The mechanism by which proton pump inhibitors exert a protective effect is nonetheless unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the role of acid secretion in esophageal epithelial damage, proton pump inhibitors appear to be actually the only treatment that can interfere with the worsening of histological damage. Indeed, numerous studies have shown that acid-suppressing proton pump inhibitor therapy stabilizes the activity of cellular proliferative cells in the BE and consequently can prevent dysplasia and have a positive impact on reducing the risk of cancer in the esophagus [ 61 , 62 , 63 , 64 , 65 , 66 ] especially if the therapy is continuous and long-term [ 67 ]. The mechanism by which proton pump inhibitors exert a protective effect is nonetheless unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Metaplasia describes transformation of a fully differentiated cell type into other cell types as tissues change into entirely different tissue types. The concept gained popularity in the 1800s, was based on histological and anatomical observations, and is often discussed in terms of pathological changes in tissue in response to environmental insult such as with Barrett’s esophagus (Zhang et al 2021) or in the context of cancer as reviewed (Giroux and Rustgi 2017). However, recent evidence suggests that metaplasia and cellular plasticity contribute to development and regeneration within the musculoskeletal system and beyond (Kaji et al 2020; Brown et al 2022; Goldenring and Mills 2022).…”
Section: Paligenosis: a Process Of Metaplasia In Multicellular Organismsmentioning
confidence: 99%
“…Gastric mucosal IM is a pathological process in which intestinal epithelial cells replace gastric mucosal epithelial cells, that is, there are epithelial cells similar to the intestinal mucosa in the gastric mucosa (Abdelfattah et al, 2021 ; Jonaitis et al, 2021 ; Zhang et al, 2021 ; He et al, 2022 ). IM is common in the stomach and esophagus, but can also be seen in the gallbladder, bile duct, uterus, bladder, pelvis, ureter, and urethra (Deniz et al, 2010 ; Rubio et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%